2017
DOI: 10.21127/yaoyigc20170013
|View full text |Cite
|
Sign up to set email alerts
|

 Progress of Liposomal Nanohybrid Cerasomes as Novel Drug Nanocarriers

Abstract: Despite many benefits, liposomes have still not realized their full potential as vehicles for drug delivery due to the morphological instability. Recently, liposomal nanohybrid cerasomes have been developed as novel drug nanocarriers based on organoalkoxysilane through a sol-gel reaction in combination with self-assembly process. The presence of polyorganosiloxane network on the surface imparts cerasomes higher morphological stability than conventional liposomes and the incorporation of liposomal bilayer struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Moreover, the hybrid cerasome presents significantly reduced overall rigidity and density due to its liposomal bilayer rendering it more biocompatible and biodegradable than neat silica nanoparticles (Yue & Dai, ). Another unique advantage of cerasomes is their ability to functionalize the silanols located on the exterior surface to allow easy bioconjugation of biomolecules (Hameed, Bhattarai, & Dai, ; S. Li et al, ; Yue, Jing, & Dai, ). Furthermore, thermosensitive cerasomes (Liang et al, ) and redox responsive cerasomes (G. Zhou et al, ) for effective cancer treatments are reported.…”
Section: Different Types Of Oinhsmentioning
confidence: 99%
“…Moreover, the hybrid cerasome presents significantly reduced overall rigidity and density due to its liposomal bilayer rendering it more biocompatible and biodegradable than neat silica nanoparticles (Yue & Dai, ). Another unique advantage of cerasomes is their ability to functionalize the silanols located on the exterior surface to allow easy bioconjugation of biomolecules (Hameed, Bhattarai, & Dai, ; S. Li et al, ; Yue, Jing, & Dai, ). Furthermore, thermosensitive cerasomes (Liang et al, ) and redox responsive cerasomes (G. Zhou et al, ) for effective cancer treatments are reported.…”
Section: Different Types Of Oinhsmentioning
confidence: 99%